Analisis Layanan Komunikasi Antara Customer Service Dan Driver Gojek (Studi Pada Kantor Gojek Cabang Palembang) - Muhammad Randicha Hamandia; Sri Hertimi; Varhan Alfitho (Journal of Media and Communication | E-ISSN : 3063-9581, 2025)
This study aims to analyze the communication service between Customer Service (CS) and Gojek drivers at the Gojek branch office in Palembang. The research employs a qualitative descriptive approach using observation, interviews, and documentation involving CS officers, office coordinators, field task forces, and partner drivers. The findings reveal that communication between CS and drivers is effective and fosters a positive working relationship. Through the narrative analysis approach, the interaction reflects an exchange of information that is both technical and emotional. The communication convergence theory shows that CS adapts their language style and communication attitude to be closer to drivers, while the excellent service theory demonstrates politeness, empathy, and responsiveness in handling complaints. The integration of these three perspectives creates humanistic, professional, and solution-oriented communication, enhancing driver satisfaction and loyalty toward the company.